SCOPING REVIEW ON OUTCOMES OF BALLOON SINUPLASTY IN THE TREATMENT OF CHRONIC RHINOSINUSITIS (Vietnam Journal of Community Medicine, 2026)
Objective: To study the results of using balloon sinusplasty in the treatment of chronic rhinosinusitis. Subjects and methods: All articles worldwide on the use of balloon sinusplasty in the treatment of chronic rhinosinusitis from 2005 to 2026. Methods: Scoping review using the PRISMA-ScR checklist, updated to April 2026.Results: Eleven studies involving 695 patients were included. Studies originated from Asia (45.5%), Europe (27.3%), and the Americas (27.3%), predominantly using prospective interventional designs without control groups (36.4%). BSP demonstrated clinically significant symptom improvement, with SNOT-22 score reductions ranging from 17.6 to 43 points and SNOT-20 reductions from 1.57 to 2.5 points. Success rates ranged from 62% to 96.7%. Complications were mostly mild with no serious adverse events reported. Recurrence rates ranged from 1.3% to 22% depending on follow-up duration.Conclusion: Balloon sinus dilation is an effective and safe method for treating mild to moderate chronic rhinosinusitis and may be considered as an option in some cases before endoscopic sinus surgery
Keywords: Chronic rhinosinusitis, balloon sinuplasty, scoping review.